You cannot copy content of this page

NCERT solution class 7 chapter 12 Algebraic expressions 12.2 mathematics

EXERCISE 12.2


Page No 239:

Question 1:

Simplify combining like terms:

(i) 21b − 32 + 7b − 20b

(ii) − z2 + 13z2 − 5z + 7z3 − 15z

(iii) p − (p − q) − q − (− p)

(iv) 3a − 2b − ab − (a − b + ab) + 3ab + b − a

(v) 5x2y − 5x2 + 3y x2 − 3y2 + x− y+ 8xy2 −3y2

(vi) (3 y+ 5y − 4) − (8y − y2 − 4)

Answer:

(i) 21b − 32 + 7− 20b = 21b + 7− 20b − 32

b (21 + 7 − 20) −32

= 8b − 32

(ii) − z2 + 13z2 − 5z + 7z3 − 15z = 7z3 − z2 + 13z2 − 5z − 15z

= 7z3 + z2 (−1 + 13) + z (−5 − 15)

= 7z3 + 12z2 − 20z

(iii) p − (p − q) − q − (q − p) = p − p + q − q − q + p

− q

(iv) 3a − 2b − ab − (a − b + ab) + 3ba + − a

= 3a − 2b − ab − a + b − ab + 3ab + − a

= 3a − a − a − 2b + b − ab − ab + 3ab

a (3 − 1 − 1) + b (− 2 + 1 + 1) + ab (−1 −1 + 3)

a + ab

(v) 5x2y − 5x2 + 3yx2 − 3y2 + x2 − y2 + 8xy2 − 3y2

= 5x2y + 3yx− 5x2 + x2 − 3y2 − y2 − 3y+ 8xy2

x2(5 + 3) + x2 (−5 + 1) + y2(−3 − 1 − 3) + 8xy2

= 8x2y − 4x2 − 7y2 + 8xy2

(vi) (3y+ 5y − 4) − (8y − y2 − 4)

= 3y2 + 5y − 4 − 8y + y2 + 4

= 3y2 + y2 + 5y − 8y − 4 + 4

y2 (3 + 1) + y (5 − 8) + 4 (1 − 1)

= 4y2 − 3y

Question 2:

Add:

(i) 3mn, − 5mn, 8mn, −4mn

(ii) − 8tz, 3tz − zz − t

(iii) − 7mn + 5, 12mn + 2, 9mn − 8, − 2mn − 3

(iv) a + b − 3, b − a + 3, a − b + 3

(v) 14x + 10y − 12xy − 13, 18 − 7x − 10+ 8xy, 4xy

(vi) 5m − 7n, 3n − 4m + 2, 2m − 3mn − 5

(vii) 4x2y, − 3xy2, − 5xy2, 5x2y

(viii) 3p2q2 − 4pq + 5, − 10p2q2, 15 + 9pq + 7p2q2

(ix) ab − 4a, 4b − ab, 4a − 4b

(x) x− y2 − 1 , y2 − 1 − x2, 1− x2 − y2

Answer:

(i) 3mn + (−5mn) + 8mn + (−4mn) = mn (3 − 5 + 8 − 4)

= 2mn

(ii) (t − 8tz) + (3tz − z) + (z − t) = t − 8tz + 3tz − z + z − t

− t − 8tz + 3tz − z + z

t (1 − 1) + tz (− 8 + 3) + z (− 1 + 1)

= −5tz

(iii) (− 7mn + 5) + (12mn + 2) + (9mn − 8) + (− 2mn − 3)

= − 7mn + 5 + 12mn + 2 + 9mn − 8 − 2mn − 3

= − 7mn + 12mn + 9mn − 2mn + 5 + 2 − 8 − 3

= mn (− 7 + 12 + 9 − 2) + (5 + 2 − 8 − 3)

= 12mn − 4

(iv) (a + − 3) + (b − a + 3) + (a − b + 3)

a + − 3 + b − a + 3 + a − b + 3

a − a + a + − − 3 + 3 + 3

a (1 − 1 + 1) + b (1 + 1 − 1) + 3 (− 1 + 1 + 1)

a + b + 3

(v) (14+ 10y − 12xy − 13) + (18 − 7x − 10y + 8yx) + 4xy

= 14+ 10y − 12xy − 13 + 18 − 7x − 10y + 8yx + 4xy

= 14− 7x + 10y − 10y − 12xy + 8yx + 4xy − 13 + 18

= x (14 − 7) + (10 − 10) + xy (− 12 + 8 + 4) − 13 + 18

= 7x + 5

(vi) (5m − 7n) + (3n − 4m + 2) + (2m − 3mn − 5)

= 5m − 7n + 3n − 4m + 2 + 2m − 3mn − 5

= 5m − 4m + 2m − 7n + 3n − 3mn + 2 − 5

m (5 − 4 + 2) + n (− 7 + 3) −3mn + 2 − 5

= 3m − 4n − 3mn − 3

(vii) 4x2 − 3xy2 − 5xy2 + 5x2y = 4x2 + 5x2y − 3xy2 − 5xy2

x2 y (4 + 5) + xy2 (− 3 − 5)

= 9x2y − 8xy2

(viii) (3p2q2 − 4pq + 5) + (−10 p2q2) + (15 + 9pq + 7p2q2)

= 3p2q2 − 4pq + 5 − 10 p2q2 + 15 + 9pq + 7p2q2

= 3p2q2 − 10 p2q+ 7p2q− 4pq + 9pq + 5 + 15

p2q2 (3 − 10 + 7) + pq (− 4 + 9) + 5 + 15

= 5pq + 20

(ix) (ab − 4a) + (4− ab) + (4a − 4b)

ab − 4a + 4− ab + 4a − 4b

ab − ab − 4+ 4a + 4− 4b

ab (1 − 1) + a (− 4 + 4) + b(4 − 4)

= 0

(x) (x2 − y2 − 1) + (y2 − 1 − x2) + (1 − x2 − y2)

x2 − y2 − 1 + y2 − 1 − x2 + 1 − x2 − y2

x2 − x− x− y2 + y− y− 1 − 1 + 1

x2(1 − 1 − 1) + y2 (−1 + 1 − 1) + (− 1 − 1 + 1)

= − x2 − y2 − 1

Page No 240:

Question 3:

Subtract:

(i) − 5yfrom y2

(ii) 6xy from − 12xy

(iii) (a − b) from (b)

(iv) a (b − 5) from b (5 − a)

(v) − m2 + 5mn from 4m2 − 3mn + 8

(vi) − x2 + 10x − 5 from 5x − 10

(vii) 5a2 − 7ab + 5b2 from 3ab − 2a2 −2b2

(viii) 4pq − 5q2 − 3p2 from 5p2 + 3q− pq

Answer:

(i) y2 − (−5y2) = y2 + 5y2 = 6y2

(ii) − 12xy − (6xy) = −18xy

(iii) (a + b) − (a − b) = a + − a + = 2b

(iv) b (5 − a) − a (b − 5) = 5b − ab − ab + 5a

= 5a + 5b − 2ab

(v) (4m2 − 3mn + 8) − (− m2 + 5mn) = 4m2 − 3mn + 8 + m2 − 5 mn

= 4m2 + m2 − 3mn − 5 mn + 8

= 5m2 − 8mn + 8

(vi) (5x − 10) − (− x2 + 10x − 5) = 5− 10 + x2 − 10x + 5

x2 + 5− 10x − 10 + 5

x2 − 5− 5

(vii) (3ab − 2a2 − 2b2) − (5a2− 7ab + 5b2)

= 3ab − 2a2 − 2b2 − 5a2 + 7ab − 5 b2

= 3ab + 7ab − 2a− 5a2 − 2b2 − 5 b2

= 10ab − 7a2 − 7b2

(viii) 4pq − 5q2 − 3p2 from 5p2 + 3q2 − pq

(5p2 + 3q2 − pq) − (4pq − 5q2− 3p2)

= 5p2 + 3q2 − pq − 4pq + 5q2 + 3p2

= 5p2 + 3p2 + 3q2 + 5q2 − pq − 4pq

= 8p2 + 8q2 − 5pq

Question 4:

(a) What should be added to x2 + xy + y2 to obtain 2x2 + 3xy?

(b) What should be subtracted from 2+ 8b + 10 to get − 3a + 7b + 16?

Answer:

(a) Let a be the required term.

a + (x2 + y2 + xy) = 2x+ 3xy a = 2x2 + 3xy − (x2 + y2 + xy)

a = 2x2 + 3xy − x2 − y2 − xy

a = 2x2 − x2 − y2 + 3xy − xy

x2 − y2 + 2xy

(b) Let p be the required term.

(2a + 8b + 10) − = − 3a + 7b + 16

p = 2a + 8b + 10 − (− 3a + 7b + 16)

= 2a + 8b + 10 + 3a − 7− 16

= 2a + 3a + 8b − 7b + 10− 16

= 5− 6

Question 5:

What should be taken away from 3x2 − 4y2 + 5xy + 20 to obtain

− x2 − y+ 6xy + 20?

Answer:

Let p be the required term.

(3x2 − 4y2 + 5xy + 20) − p = − x2 − y2 + 6xy + 20

p = (3x2 − 4y2 + 5xy + 20) − (− x2 − y2 + 6xy + 20)

= 3x2 − 4y2 + 5xy + 20 + x2 + y2 − 6xy − 20

= 3x2 + x− 4y2 + y2 + 5xy − 6xy + 20 − 20

= 4x2 − 3y2 − xy

Question 6:

(a) From the sum of 3x − y + 11 and − y − 11, subtract 3x − y − 11.

(b) From the sum of 4 + 3x and 5 − 4x + 2x2, subtract the sum of 3x2 − 5x and − x2 + 2x + 5.

Answer:

(a) (3x − y + 11) + (− y − 11)

= 3x − + 11 − y − 11

= 3x − − y + 11 − 11

= 3x − 2y

(3x − 2y) − (3x − − 11)

= 3x − 2y − 3x + + 11

= 3x − 3x − 2y + + 11

= − y + 11

(b) (4 + 3x) + (5 − 4x + 2x2) = 4 + 3x + 5 − 4x + 2x2

= 3x − 4x + 2x2 + 4 + 5

= − x + 2x2 + 9

(3x2 − 5x) + (− x2 + 2x + 5) = 3x2 − 5x − x2 + 2x + 5

= 3x2 − x− 5x + 2x + 5

= 2x2 − 3x + 5

(− x + 2x2 + 9) − (2x2 − 3x + 5)

= − x + 2x2 + 9 − 2x2 + 3x − 5

= − x + 3x + 2x2 − 2x+ 9 − 5

= 2x + 4

Leave a Comment

Your email address will not be published. Required fields are marked *

error: Content is protected !!
Free Web Hosting